International relations of Asia - Shambaugh, David L.; Yahuda, Michael B.; Shambaugh, David L.; IG Publishing Online (Online service). (Lanham Rowman & Littlefield, 2014)
"As the world's most dynamic region, Asia embodies explosive economic growth, diverse political systems, vibrant societies, modernizing militaries, cutting-edge technologies, rich cultural traditions amid globalization, and strategic competition among major powers. As a result, international relations in Asia are evolving rapidly. In this fully updated and expanded volume, leading scholars from Asia, Europe, and North America offer the most current and definitive analysis available of Asia's regional relationships. They set developments in Asia in theoretical context, assess the role of leading external and regional powers, and consider the importance of subregional actors and linkages".
International relations in Asia : a multidimensional analysis / David Shambaugh -- The evolving Asian system : three transformations / Samuel S. Kim -- Thinking theoretically about Asian IR / Amitav Acharya -- The United States in Asia : durable leadership / Robert Sutter -- Europe's role in Asia : distant but involved / Sebastian Bersick -- China's role in Asia : attractive or assertive? / Phillip C. Saunders -- India's role in Asia : a rising regional power / T.V. Paul -- Japan's role in Asia : searching for certainty / Michael Green -- ASEAN and Southeast Asia : remaining relevant / Sheldon W. Simon -- Australia's choices in the Asian century / Hugh White -- Central Asia : the end of the "great game"? / Martha Brill Olcott -- The Korean Peninsula and Northeast Asian stability / Scott Snyder -- The Asian regional economy / Edward J. Lincoln -- Globalization and international relations in Asia / Nayan Chanda -- Security dynamics in East Asia / Ralph A. Cossa -- Looking ahead : a new Asian order? / Michael Yahuda.
Includes bibliographical references and index.
Keywords: Electronic books; Asia -- Politics and government -- 21st century; Asia -- Foreign relations